EIRP Characterization of Electrically Large Wireless Equipment with Integrated Signal Generator in a Compact Environment - Soon-Soo Oh; Woo-Su Kim; Young-Hwan Lee (International Journal of Antennas and Propagation)
We describe a measurement technique to characterize the equivalent isotropically radiated power (EIRP) of electrically large wireless equipment in a compact environment. A modified phase-measurement method was proposed and, thus, the separation of the signal generator and radiating element was not required during the measurement. A Fresnel-to-far-field transformation was used for the fast measurement time in a compact anechoic chamber. An experimental verification of the method was carried out in a compact anechoic chamber, where the source-detector separation was approximately 1/5 of the far-field distance. The measured magnitude and phase pattern exhibited only a small error. The EIRP obtained using a Fresnel-to-far-field transformation was compared with a reference value, and the error was within 0.5 dB.